Learning Video on Indonesian Cultural Diversity Based on Mekotek Local Wisdom - Sastrawan, I Ketut Gede Putra; Sujana, I Wayan (Universitas Pendidikan Ganesha, 2024)
The lack of use of technology and learning media in the learning process reduces students' interest and enthusiasm for learning. Therefore, media is needed in the form of learning videos for fourth grade elementary school students to overcome problems. This study aims to develop video media for learning about Indonesian cultural diversity based on Mekotek local wisdom. The type of research carried out is development research using a development model, namely the ADDIE model. Data collection methods were carried out through interview methods, questionnaire/questionnaire methods, and test methods in the form of multiple choice questions. The results of this research are the design of learning video media based on the assessment results from design and construction experts of 93.18% with very good qualifications. Learning media was declared feasible based on the assessment results from subject content experts of 90.38% with very good qualifications, the assessment results of instructional design experts of 90% with very good qualifications, the assessment results of learning media experts of 90% with very good qualifications, the results of the individual trial assessment were 90% with very good qualifications, and the results of the small group trial assessment were 90.2% with good qualifications. The effectiveness of the Learning Video based on the t-test results obtained tcount = -10.418 for db = 46 and a significance level of 5% = 1.679. This means tcount > ttable, so H0 is rejected and H1 is accepted. So it can be concluded that the cultural diversity video media based on Mekotek local wisdom is effectively used in science subjects for students.